Vaccination as an immune system status optimization tool for the high-performance sports: review - I. V. Konovalov; A. V. Zholinsky; S. P. Alpatov; A. V. Zorenko; N. V. Tochtieva; B. K. Romanov; S. A. Parastaev (National Electronic Information Consortium (NEICON), 2022)
Objective: consideration of the importance of vaccination as a preventive measure of support the athlets immunne system in conditions of extreme physical exertion and increased epidemic risks.Materials and methods: analysis of local and foreign dates of immunocorrection and vaccination problems.Results: the presented review provides an integral assessment of the transitory immunosuppression, developing by the intensive training and competitive activities - exercise-induced immunosuppression. These dates described as an "open window" syndrome and characterized by an increased risk of viral and/or bacterial infection with predominant damage of the upper respiratory tract and gastrointestinal tract. Widespread immunoprophylaxis provides an effective and relatively safe method of infectious control at risk groups including athletes.Conclusion: Vaccines of National Immunization Schedule and Epidemiological Immunization Schedule provide complex impact to the athletes immune status in wide variety of physical and psychological stresses. Vaccination increases the ability of specific and nonspecific resistance to infections that provide significant prevention of the "open window" syndrome.